Analysis Of Higher Order Thinking Skills In The Lesson Plan (RPP) By Class V Teachers On Theme 6 Sub Theme 3 At Inpres Gantarang Elementary School Gowa Regency - Nurhaedah, Nurhaedah; Irfan, Muhammad; Muliana, Muliana (Program Studi PGSD FIP UNM, 2023)
The purpose of this study is to determine the description of higher-order thinking skills in RPP Theme 6 Subtheme 3 class V SD Inpres Gantarang District Tinggimoncong Gowa Regency by analyzing : (1) Operational verbs on the components of Competency Achievement Indicators ;(2) Operational verbs on learning objectives; and (3) steps of learning activities. Analysis of Higher Order Thibnking Skills (HOTS) of Operational Verbs on indicators and learning objectives refers to the cognitive level of Bloom's Taxonomy, while analysis on the steps of learning activities refers to critical thinking criteria. This research uses a qualitative approach with a type of document study research and uses qualitative descriptive research methods. The focus of this research is the Learning Implementation Plan for grade V teachers theme 6 subtheme 3 SD Inpres Gantarang. The data collection technique in this study is by documentation study. The results showed that: (1) The description of HOTS in the Competency Achievement Indicators section, namely Operational Verbs used is still dominated by low cognitive levels C1-C3; (2) The description of HOTS in Learning Objectives also still uses operational verbs dominated by low cognitive levels C1-C3; (3) The description of HOTS in the learning activity step is that the teacher has included activities that invite students to think higher level when viewed based on critical thinking criteria.